Intra‐articular injection of triamcinolone acetonide sustains macrophage levels and aggravates osteophytosis during degenerative joint disease in mice. (26th January 2022) - Ferrao Blanco, Mauricio N.; Bastiaansen Jenniskens, Yvonne M.; Kops, Nicole; Chavli, Athina; Narcisi, Roberto; Botter, Sander M.; Leenen, Pieter J. M.; van Osch, Gerjo J. V. M.; Fahy, Niamh
Abstract : Background and purpose: Corticosteroids such as triamcinolone acetonide (TAA) are potent drugs administered intra‐articularly as an anti‐inflammatory therapy to relieve pain associated with osteoarthritis (OA). However, the ability of early TAA intervention to mitigate OA progression and modulate immune cell subsets remains unclear. Here, we sought to understand the effect of early intra‐articular injection of TAA on OA progression, local macrophages, and peripheral blood monocytes. Experimental approach: Degenerative joint disease was induced by intra‐articular injection of collagenase into the knee joint of male C57BL/6 mice. After 1 week, TAA or saline was injected intra‐articularly. Blood was taken throughout the study to analyse monocyte subsets. Mice were killed at days 14 and 56 post‐induction of collagenase‐induced OA (CiOA) to examine synovial macrophages and structural OA features. Key results: The percentage of macrophages relative to total live cells present within knee joints was increased in collagenase‐ compared with saline‐injected knees at day 14 and was not altered by TAA treatment. However, at day 56, post‐induction of CiOA, TAA‐treated knees had increased levels of macrophages compared with the knees of untreated CiOA‐mice. The distribution of monocyte subsets present in peripheral blood was not altered by TAA treatment during the development of CiOA. Osteophyte maturation was increased in TAA‐injected knees at day 56. Conclusion and implications: Intra‐articular injection of TAA increases long‐term synovial macrophage numbers and osteophytosis. Our findings suggest that TAA accentuates the progression of osteoarthritis‐associated features when applied to an acutely inflamed knee.